2001
DOI: 10.1021/es0014943
|View full text |Cite
|
Sign up to set email alerts
|

A Continuous System for Fe0 Reduction of Nitrobenzene in Synthetic Wastewater

Abstract: Nitrobenzene is a major environmental pollutant, and its degradation is difficultto achieve. Hence, a chemical reduction pretreatment is sought in this research, before the resulting aniline can be treated by enzyme-mediated oxidative polymerization. Zerovalent iron (Fe0) has been successfully employed to reduce nitrobenzene to aniline in synthetic wastewater in both batch and continuous flow reactors. The concentration of nitrobenzene studied was thatwhich would be present in industrial wastewater streams (mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(83 citation statements)
references
References 33 publications
3
78
0
Order By: Relevance
“…It was well known that anhydrous sodium sulfite (Na2SO3) is capable of scavenging DO effectively and has long been used in the presence of a catalyst (CoCl2) to scavenge DO in water [13]. According to the chemical Equation (1), the suitable weight of Na2SO3 was determined by considering the water volume in the system, the present DO concentration, and its desired value.…”
Section: Experimental Procedures and Phenomenamentioning
confidence: 99%
“…It was well known that anhydrous sodium sulfite (Na2SO3) is capable of scavenging DO effectively and has long been used in the presence of a catalyst (CoCl2) to scavenge DO in water [13]. According to the chemical Equation (1), the suitable weight of Na2SO3 was determined by considering the water volume in the system, the present DO concentration, and its desired value.…”
Section: Experimental Procedures and Phenomenamentioning
confidence: 99%
“…It strongly masks the real mechanisms of contaminant removal as that is a complex interplay between Fe 0 particles, Fe II released into solution and Fe II /Fe III precipitation [89][90][91][92][93][94][95][96]. In particular, the transformation of Fe 0 to Fe oxides goes through colloids and hydroxides.…”
Section: Contaminant Removal In Fe 0 /H 2 O Systemsmentioning
confidence: 99%
“…On the other hand, regarding the abundance of (partly nascent) adsorbing sites and continuous generation of Fe II species, contaminant chemical reduction by so-called structural Fe II (adsorbed Fe II ) is favored [96]. The abundance of Fe II /Fe III hydroxides/oxides in Fe 0 /H 2 O systems has been experimentally demonstrated by [92]. However, the authors have suggested adsorptive removal as an important removal mechanism accompanying direct reduction, which is in contradiction to the mechanisms presented in Section 2.…”
Section: Contaminant Removal In Fe 0 /H 2 O Systemsmentioning
confidence: 99%
“…In an independent approach, Fe 0 was used as a reducing agent or generator of iron hydroxides for water treatment [33][34][35]. By 2002, Fe 0 had already been tested for many relevant groups of chemical contamination.…”
Section: The Suitability Of Fe 0 Filters For Safe Water Provision In mentioning
confidence: 99%